Amidst Global Uncertainty: Does Islamic Banking Increase Indonesia’s Economic Growth? - Maddani Akhsa Nulyani; Julia Noermawati Eka Satyarini; Muhammad Ady Mahfuzh; Nurfitri Harkunti Kemala Hayati; Mochamad Rizki (Department of Islamic Economics, IPB University, 2025)
Global economic uncertainty has caused shocks in various economic sectors in Indonesia. The establishment of Islamic banking in Indonesia is projected to address and mitigate the challenges posed by global economic uncertainty. Our study aims to to evaluate the financial performance of Islamic banking institutions by employing the RGEC methodology, encompassing variables such as risk profile, Good Corporate Governance (GCG), earning ratios, and capital ratios. The proposed hypotheses were assessed through panel data regression employing the Random Effect Model (REM) approach. The findings reveal that, partially, GCG, NOM, and CAR exhibit a significant negative influence on economic growth, while ROA demonstrates a significant positive impact on Indonesia's economic expansion. Conversely, NPF, and BOPO do not exhibit significant effects, but overall, the robust financial performance of Islamic banks is a pivotal factor in accelerating Indonesia's economic growth. This study emphasizes on Islamic banks in Indonesia, drawing data from twelve Islamic commercial banks, thus establishing a solid empirical basis for addressing global economic uncertainty and facilitating more valid generalizations pertinent to the Indonesian Islamic banking sector. It is imperative for the government and relevant entities to consistently ensure that Islamic banks effectively fulfill their intermediary role and expand their market share, thereby enhancing economic growth in Indonesia.